PPP vs ODA revisited key issues for PPP infrastructure development in the Philippines - Ito, Susumu (2018)
This paper studies key issues for infrastructure development in the Philippines by focusing on a major policy shift on public-private partnership (PPP) from the Aquino administration to the Duterte administration. While the former focused on PPP-based infrastructure development as a priority policy, the Duterte administration in 2017 launched “Dutertenomics”, a large-scale infrastructure development plan of about ₱8 trillion, about $160 billion, over 6 years which mainly depends on the national budget and Official Development Assistance (ODA) as a financial source rather than PPP. This triggered a debate on “PPP vs ODA” in the Philippines.

The paper discusses that it is not about the “PPP vs ODA”, but how to promote complementary relations between the public and PPP; in other words, “PPP and ODA”. In this context, the PPP environment will be evaluated based on four criteria: regulatory framework; institutional framework; institutional capacity; and financial facilities. Key issues for further improvement of the PPP environment in the Philippines will be also discussed for policy recommendations including enactment of PPP law, government guarantee for contingent liability, foreign capital deregulation, risk-sharing mechanism, development of “bankable” project, and development of capital market.
Keywords: Public-private sector cooperation; Official Development Assistance; Economic development projects